ENHANCING CLASSROOM ENGAGEMENT USING ONLINE GAMES - Tri Pujiani; Ida Dian Sukmawati (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
In recent years, technology has become increasingly integrated into educational settings. As technology continues to evolve, educators will need to stay abreast of new developments and find innovative ways to integrate technology into the learning experience. One example of technological integration into learning activities is the utilization of online games. This study aimed to give an overview of the most commonly used online educational games and their impact on enhancing classroom engagement. This research was descriptive-qualitative, applying both theoretical and empirical approaches. A literature review was conducted to study and interpret the available research papers on the topic. To be more comprehensive, questionnaires were distributed to find out the overview of online games commonly used in the classroom and the students' engagement with this teaching method. The results of this study confirmed that there is a positive correlation between the use of online games and classroom engagement. This study recommends online games be applied in order to enrich the practice of English language teaching (ELT). Further study on the characteristics, strengths, and weaknesses of these games is still required to help educators choose the best game that meets the learning objectives and students' needs.